Studi Literatur: Pengaruh Diet Mediterania terhadap Profil Lipid dan Glukosa Darah Puasa pada Orang Overweight atau Obesitas: Literature Review: The Effect of Mediterranean Diet on Lipid Profile and Fasting Blood Glucose in Overweight or Obese - Gustina Berta Uli; Sekar Ramadhanti Asyahir; Leny Budhi Harti (Universitas Airlangga, 2023)
Background: National Basic Health Research or Riset Kesehatan Dasar in 2018 stated that obesity in Indonesia had reached 21.8%. Being overweight and obese are among the risk factors that increase various health problems, including dyslipidemia and type 2 diabetes mellitus; hence, lifestyle changes are needed, one of which is through dietary modification. The Mediterranean diet is said to improve the lipid and glucose profiles of overweight or obese people. Objectives: This literature study aimed to determine the effect of the Mediterranean diet on lipid profiles and blood glucose levels of overweight or obese people. Methods: This research was conducted using the literature review method on two databases that consist of Pubmed and Cochrane, with specific keywords: